2010
DOI: 10.1016/j.bbamem.2010.07.017
|View full text |Cite|
|
Sign up to set email alerts
|

The yeast permease Acr3p is a dual arsenite and antimonite plasma membrane transporter

Abstract: The Acr3p permease from the yeast Saccharomyces cerevisiae is a prototype member of the arsenical resistance-3 (Acr3) family of transporters, which are found in all domains of life. Remarkably little is known about substrate specificity, localization and regulation of Acr3 proteins. Here, we show that the yeast Acr3p mediates not only high-level resistance to arsenite but also moderate tolerance to antimonite. The acr3 deletion mutant shows increased sensitivity to antimonite. In addition, overexpression of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 42 publications
1
29
0
4
Order By: Relevance
“…The arsenic sensing and signaling events mediated by activation of Hog1p and Fps1p contribute to the tolerance of arsenic acquisition. Wysocki, R., Bobrowicz, P., & Ulaszewski, S. (1997) first showed that Fps1p facilitates efflux of As(III) out of cells and is essential to maintain As(V) resistance (Maciaszczyk-Dziubinska, E., Migocka, M., & Wysocki, R. (2012)). As(V) enters the yeast cell through phosphate transporters (Bun-ya et al, 1996).…”
Section: Uptake Systems For Arsenicmentioning
confidence: 99%
See 1 more Smart Citation
“…The arsenic sensing and signaling events mediated by activation of Hog1p and Fps1p contribute to the tolerance of arsenic acquisition. Wysocki, R., Bobrowicz, P., & Ulaszewski, S. (1997) first showed that Fps1p facilitates efflux of As(III) out of cells and is essential to maintain As(V) resistance (Maciaszczyk-Dziubinska, E., Migocka, M., & Wysocki, R. (2012)). As(V) enters the yeast cell through phosphate transporters (Bun-ya et al, 1996).…”
Section: Uptake Systems For Arsenicmentioning
confidence: 99%
“…Fungal members of this family include the ScAcr3p metalloid efflux protein from S. cerevisiae , which was proposed to be selective for As(III) over Sb(III) (Maciaszczyk, Wysocki, Golik, Lazowska, & Ulaszewski, 2004). Recently, ScAcr3p has been suggested to transport Sb(III) in vivo as well (Maciaszczyk-Dziubinska et al, 2012), and yeast plasma membrane vesicles accumulate both As(III) and Sb(III) by exchange with protons (Maciaszczyk-Dziubinska et al, 2012). However, other data indicating that Sb(III) is not transported in yeast plasma membrane vesicles are not in agreement with that conclusion (Ghosh et al, 1999), and bacterial Acr3 orthologues appear to be specific for As(III) and do not transport Sb(III) (Fu et al, 2009; Villadangos et al, 2012).…”
Section: Efflux Systems For Arsenicmentioning
confidence: 99%
“…Two yeast (Saccharomyces cerevisiae) strains derived from BY4741 were used in this study; the ΔSKN7 strain that has an impaired oxidative stress defense response and is sensitive to H 2 O 2 (Bienert et al 2007) and the ΔACR3 strain that lacks an arsenite extrusion transporter (Maciaszczyk-Dziubinska et al 2010) and is sensitive to arsenite (Bienert et al 2007). Before the introduction of pYES2 (Invitrogen), cells were culture with YPAD medium (1% bacto yeast extract (Difco), 2% bacto peptone (Difco), 2% glucose and 27 µM adenine (Sigma)).…”
Section: Yeast Strains and Growthmentioning
confidence: 99%
“…Based on these observations it has been concluded that Acr3 confers tolerance to arsenicals by mediating extrusion of As(III) out of the cell (Figure 1). Recently, we have shown that Acr3 is indeed localized to the yeast plasma membrane [82]. In addition, we have demonstrated that As(III) uptake into inside-out plasma membrane vesicles prepared from the Acr3-expressing yeast cells is coupled to the electrochemical potential gradient of protons generated by the plasma membrane H + -ATPase [83].…”
Section: Transporters For As(iii) and Sb(iii) Detoxificationmentioning
confidence: 99%